THE INFLUENCE OF COMPANY SIZE, CURRENT RATIO, TATO AND DER ON PROFITABILITY - Nina Purnasari; Devi -; Delpita Simanjuntak; Dede Aryanto B Manalu (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This observation is useful in examining how the impact of company size, CR, TATO, DER on profitability in the consumer goods industry sector companies listed on the IDX for the 2016-2019 period. The data used in the form of financial information each year is published from the company on the IDX website. Examples in this observation consist of 31 companies and 124 data. These observations require multiple linear regression analysis models, T test, F test, least squares equation. The results of these observations can be obtainedR2a number of 0.197 means the profitability variable that can be explained in the company size variable, CR, TATO, DER of 19.7%, then the rest is influenced by other variables. The results of the discussion state that partially company size, TATO, DER have a significant impact even though CR does not have a significant impact on profitability. And simultaneously company sizes, CR, TATO, DER have a significant impact on profitability